Pengaruh Pengetahuan &Persepsi Keadilan Pajak Terhadap Niat Membayar Pajak Mahasiswa Di Palembang - Stevani Stevani; Kathryn Sugara (MDP Student Conference, 2026)
This study aims to determine the tax payingt intentions of university students in Palembang. The sampling method in this study uses non-probability sampling. This study uses Multiple linear regression analysis. The results showed that tax knowledge and perceptions of tax fairness have a positive and significant effect on tax paying intention